Calorimeter for Real-Time Dosimetry of Pulsed Ultra-High Dose Rate Electron Beams - Bourgouin, Alexandra; Schüller, Andreas; Hackel, Thomas; Kranzer, Rafael; Poppinga, Daniela; Kapsch, Ralf-Peter; McEwen, Malcolm (Frontiers in Physics, 2020)
An aluminium calorimeter was investigated as a possible real-time dosimeter for electron beams with ultra-high dose per pulse (DPP) as clinical applied at FLASH radiation therapy (1.5 Gy/pulse). Ion chambers, the most widely used active dosimeter type in conventional external beam radiation therapy, suffer very large ion recombination losses at these conditions. Passive dosimeters, as e.g. alanine, are independent of dose rate but do not provide real-time readout. In this work it is shown that the response of alanine is independent of the DPP in the investigated ultra-high DPP range (up to 2.3 Gy/pulse). Alanine dose measurements were then used to determine the ion recombination correction for an Advanced Markus parallel-plate ion chamber at ultra-high DPP. Ion collection losses larger than 50 % were observed. Therefore, ion chambers are not considered suitable for accurate dosimetry in FLASH radiation therapy. As alternative an aluminium open-to-atmosphere calorimeter, operated in quasi-adiabatic mode was investigated at ultra-high DPP electron radiation. The beam pulse charge, and thus the DPP, was varied to evaluate the linearity of the calorimeter response in the DPP range between 0.3 and 1.8 Gy/pulse. On average, the standard deviation of the calorimeter response was 0.1 %. The response was proportional to the DPP in the investigated range. The average deviation of